Providing pharmaceutical care remotely through medicines delivery services in community pharmacy - Oisín N. Kavanagh; Aaron Courtenay; Fatimah Khan; Deborah Lowry (Elsevier, 2022)
Background: The delivery of pharmaceutical care - and what that means - has been at the centre of many transformations of the pharmacy profession in the last century. Today, the exponential growth of pharmacies which provide pharmaceutical care exclusively online has placed increased scrutiny on the quality of the care they provide. Aim: As more patients are managed by remote pharmaceutical care (via medicines delivery services), we sought to critically evaluate this service to identify new research directions. Methods: The COnsolidated criteria for REporting Qualitative research and Standards for reporting qualitative research guideline provided the methodological framework throughout this process. Results: We reveal that although home delivery services ensure that many patients have access to their medicines, it may reduce time available to provide comprehensive pharmaceutical care, particularly in traditional brick-and-mortar pharmacies. Conclusion: We highlight a critical need for research in this area and suggest a variety of research directions: is remote pharmaceutical care a matter of convenience? Does remote pharmaceutical care help patients adhere to their medicines? How do digital health innovations impact care across patient demographics? What does comprehensive pharmaceutical care mean for patients?